Au21 cage structures and their magic number tri-cations - Ehlert, Christopher; Liu, Xiaojing J.; Hamilton, Ian (International journal of quantum chemistry, 2020)
We examine the stability and properties of three Au21 cage structures, one with D3 symmetry and denoted as Au21 (D3), which is novel, and the other two with C2v symmetry. One, denoted as Au21 (C2v-1), has been previously reported but the other, denoted as Au21 (C2v-2), is novel. As reference Au21 structures, we also examine a sheet isomer and a compact isomer, Au21 (Cs-Tetra), formed by adsorbing an Au atom on Au20 (Td). For all structures, we consider charge ranging from −1 to +4. For the Au21 cage structures, a primary property of interest is their spherical aromaticity, as measured by their nucleus independent chemical shift. Our focus is on charge +3 since each gold atom is assumed to contribute one (6s) valence electron, and 18 is a magic number for shell closing. We find that, although Au21 (D3)+3 has the largest aromaticity, it is not the most stable cage species. Surprisingly, Au21 (C2v-2), which is not even stable as a neutral cage species, is the most stable tri-cation cage species. We also examine the stability of (neutral) Au21Xn cage structures relative to Au21Xn structures derived from Au21 (Cs-Tetra) (with X = F, Cl, Br, I and n = 1, 3, 5). We find that, although Au21F3 derived from Au21 (D3) has the largest aromaticity, it is not the most stable Au21F3 cage structure. Nonetheless, all cage structures are stabilized relative to Au21 (Cs-Tetra) and, remarkably, for the trichlorinated, tribrominated, and triiodineated clusters, at least one cage structure is more stable than its Au21 (Cs-Tetra) counterpart.